Stereoselective Synthesis of the C27–C48 Moiety of Aflastatin A by a Carbohydrate Strategy Using a Tin(II)-Mediated Aldol Reaction - Murakoshi, Sawato; Hosokawa, Seijiro (Synlett, 2015)
The C27–C48 segment of aflastatin A was synthesized by using d-mannoside and l-erythrulose derivatives as chiral building blocks. The aldol reaction of undecan-2-one with mannolactone and a subsequent reduction gave the C37 and C39 stereogenic centers with high selectivity. Another aldol reaction of a tin(II) enolate of a protected erythrulose (C27–C30 segment) with a C31–C48 aldehyde segment gave the C30,C31-syn adduct with the desired stereochemistry. Deprotection of the assembled product proceeded smoothly to give the C27–C48 segment of aflastatin A containing a contiguous polyol moiety.
Keywords: stereoselectivity; aflastatin A; aldol reactions; polyols; carbohydrates